2014
DOI: 10.1063/1.4898597
|View full text |Cite
|
Sign up to set email alerts
|

Direct-bandgap GeSn grown on silicon with 2230 nm photoluminescence

Abstract: Material and optical characterizations have been conducted for epitaxially grown Ge1−xSnx thin films on Si with Sn composition up to 10%. A direct bandgap Ge0.9Sn0.1 alloy has been identified by temperature-dependent photoluminescence (PL) study based on the single peak spectrum and the narrow line-width. Room temperature PL emission as long as 2230 nm has also been observed from the same sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
131
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 24 publications
10
131
1
Order By: Relevance
“…The indirect-to-direct transition point locates at the Sn composition slightly below 10%, which agrees well with the discovery that was reported in Ref. 3; however, for relaxed GeSn samples, the transition point could happen for Sn compositions around 6%. The deviation between the Gaussian fitting points and the fitted lines are mainly due to the strain of the samples.…”
Section: Photoluminescencesupporting
confidence: 81%
See 2 more Smart Citations
“…The indirect-to-direct transition point locates at the Sn composition slightly below 10%, which agrees well with the discovery that was reported in Ref. 3; however, for relaxed GeSn samples, the transition point could happen for Sn compositions around 6%. The deviation between the Gaussian fitting points and the fitted lines are mainly due to the strain of the samples.…”
Section: Photoluminescencesupporting
confidence: 81%
“…While for the samples with higher Sn compositions, the indirect and direct peaks cannot be identified due to the small separation between the indirect and direct bandgap energies, resulting in a single peak PL spectrum with broad peak line-width. In addition, the indirect-to-direct transition occurs at the Sn composition of 10%, 3 beyond which the GeSn alloy becomes the direct bandgap material, and therefore only a direct peak with narrowed peak line-width can be observed. Note that the noisy PL spectra of GeSn samples with Sn compositions from 8% to 12% is due to the use of PbS detector, which features a 3.0 lm cut-off but with low signal-tonoise ratio.…”
Section: Photoluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence of the tendency towards a direct band structure was partially obtained in early studies. [10][11][12][13][14] However, only recently has Wirths et al demonstrated a direct bandgap alloy conclusively, with strong photoluminescence and a lasing effect at a Sn content of %11 at: %. 15 The aforementioned properties, together with the possibility of full compatibility with current Si technology, make Ge 1Àx Sn x an attractive material.…”
Section: Introductionmentioning
confidence: 99%
“…However, achieving high quality crystalline Ge 1Àx Sn x with above 6:5 at: %Sn is challenging as the material is unstable at high Sn concentration because the solid solubility of Sn in Ge at ambient temperature is about 0:5 at: % . 16 For this reason, a non-equilibrium technique is essential for growing the alloy, such as molecular beam epitaxy (MBE), 10,11,17 sputter deposition, 18 or chemical vapour deposition (CVD). 15,19,20 Alternatively, ion-beam synthesis combined with nanosecond pulsed laser melting (PLM) can also provide a condition far from equilibrium 21 for achieving supersaturated Sn concentrations in Ge.…”
Section: Introductionmentioning
confidence: 99%